2017
DOI: 10.1007/s10096-016-2892-5
|View full text |Cite
|
Sign up to set email alerts
|

Application of guidelines for aminoglycosides use in French hospitals in 2013–2014

Abstract: In 2011, the French Agency for Safety of Health Products issued guidelines underlining the principles of proper aminoglycosides' use. The aim of the survey was to evaluate adherence to these guidelines two years after their issue. Characteristics of patients receiving aminoglycosides were recorded by voluntary facilities during a 3-month survey in 2013-2014. The modalities of aminoglycosides treatment were analysed by comparison with the French guidelines. A total of 3,323 patients were included by 176 facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
1
2
0
1
Order By: Relevance
“…The evaluation still showed that the guideline found drug concentration at the peak and trough aminoglycoside in 24.9% and 67.4% of the cases, respectively. This study reinforces the use of the guideline, especially in cases with a high risk of underdosing (Robert et al, 2017).…”
Section: Discussionsupporting
confidence: 85%
“…The evaluation still showed that the guideline found drug concentration at the peak and trough aminoglycoside in 24.9% and 67.4% of the cases, respectively. This study reinforces the use of the guideline, especially in cases with a high risk of underdosing (Robert et al, 2017).…”
Section: Discussionsupporting
confidence: 85%
“…They observed that in more than one third of patients, AG indications were inappropriate and the primary indication use was concordant with the guidelines in 65.2% of the cases. Unlike our study, AG serum concentration was measured in this survey and the results showed that only, in 62.9% of the cases, the AG dose was based on the recommended range 30. In another Australian study, appropriateness of the initial dose of gentamicin dose was evaluated based on the local guidelines.…”
Section: Discussionmentioning
confidence: 88%
“…For example, in a survey-conducted study in French healthcare facilities the compliance with aminoglycoside guideline by dose was up to 60% and by therapy duration up to 90% of the patients [28]. In our study the CP recommendations were accepted only for 46% of the 85 AG1 courses needing intervention.…”
Section: Cp Consultation Characteristics Of Ag1mentioning
confidence: 50%